Investigating the exercise‐prescription practices of nurses working in inpatient mental health settings. (30th January 2015) - Stanton, Robert; Happell, Brenda; Reaburn, Peter
Abstract Nurses working in mental health are well positioned to prescribe exercise to people with mental illness. However, little is known regarding their exercise‐prescription practices. We examined the self‐reported physical activity and exercise‐prescription practices of nurses working in inpatient mental health facilities. Thirty‐four nurses completed the Exercise in Mental Illness Questionnaire – Health Practitioner Version. Non‐parametric bivariate statistics revealed no relationship between nurses' self‐reported physical activity participation and the frequency of exercise prescription for people with mental illness. Exercise‐prescription parameters used by nurses are consistent with those recommended for both the general population and for people with mental illness. A substantial number of barriers to effective exercise prescription, including lack of training, systemic issues (such as prioritization and lack of time), and lack of consumer motivation, impact on the prescription of exercise for people with mental illness. Addressing the barriers to exercise prescription could improve the proportion of nurses who routinely prescribe exercise. Collaboration with exercise professionals, such as accredited exercise physiologists or physiotherapists, might improve knowledge of evidence‐based exercise‐prescription practices for people with mental illness, thereby improving both physical and mental health outcomes for this vulnerable population.